Efficient Generation of Pathogenic A-to-G Mutations in Human Tripronuclear Embryos via ABE-Mediated Base Editing - Guanglei Li; Xinyi Liu; Shisheng Huang; Yanting Zeng; Guang Yang; Zongyang Lu; Yu Zhang; Xu Ma; Lisheng Wang; Xingxu Huang; Jianqiao Liu (Elsevier, 2019)
Base editing systems show their power in modeling and correcting the pathogenic mutations of genetic diseases. Previous studies have already demonstrated the editing efficiency of BE3-mediated C-to-T conversion in human embryos. However, the precision and efficiency of a recently developed adenine base editor (ABE), which converts A-to-G editing in human embryos, remain to be addressed. Here we selected reported pathogenic mutations to characterize the ABE in human tripronuclear embryos. We found effective A-to-G editing occurred at the desirable sites using the ABE system. Furthermore, ABE-mediated A-to-G editing in the single blastomere of the edited embryos exhibited high product purity. By deep sequencing and whole-genome sequencing, A or T mutations didn't increase significantly, and no off-target or insertion or deletion (indel) mutations were detected in these edited embryos, indicating the ABE-mediated base editing in human embryos is precise and controllable. For some sites, since a different editing pattern was obtained from the cells and the embryos targeted with the same single guide RNA (sgRNA), it suggests that ABE-mediated editing might have different specificity in vivo. Taken together, we efficiently generated pathogenic A-to-G mutations in human tripronuclear embryos via ABE-mediated base editing.